2010
DOI: 10.1515/bot.2010.008
|View full text |Cite
|
Sign up to set email alerts
|

New records of crustose seaweeds associated with subtidal maërl beds and gravel bottoms in Galicia (NW Spain)

Abstract: We studied crustose seaweeds associated with subtidal maërl beds and gravel bottoms in the Galician rías (NW Iberian Peninsula). Each species is described as well as its habitat and occurrence in maërl beds and gravel bottoms. We confirmed the great crustose species richness associated with European Atlantic maërl beds. We report a new species for the Atlantic Ocean (Contarinia peyssonneliaeformis) and six new records for the Iberian Peninsula (Atractophora hypnoides stage “Rhododiscus pulcherrimus”, Peyssonne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
0
2
0
2
Order By: Relevance
“…Moreover Dudresnaya was collected from rhodolith beds in New Zealand. As found in other regions (Amado-Filho et al 2010;Pena & Bárbara 2010) research on the algal diversity associated with this fragile habitat has revealed a number of new taxa (Nelson et al 2012). Our morphological observations fit well with the original description although our samples were slightly smaller in height.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Moreover Dudresnaya was collected from rhodolith beds in New Zealand. As found in other regions (Amado-Filho et al 2010;Pena & Bárbara 2010) research on the algal diversity associated with this fragile habitat has revealed a number of new taxa (Nelson et al 2012). Our morphological observations fit well with the original description although our samples were slightly smaller in height.…”
Section: Discussionmentioning
confidence: 80%
“…As found in other regions (Amado‐Filho et al . ; Pena & Bárbara ) research on the algal diversity associated with this fragile habitat has revealed a number of new taxa (Nelson et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…La colonización se produjo de Norte a Sur (Bárbara et al 2014), Desde las primeras citas de Mesophyllum expansum en el Atlántico ibérico (2010( -2012( , Peña et al 2015 se han detectado nuevas poblaciones en Galicia. Actualmente es una especie muy abundante en algunas localidades, cubriendo grandes extensiones de sustrato rocoso, así como epifita de partes apicales de Cystoseira baccata.…”
Section: Cyanobacteriaunclassified
“…En Galicia, diversos trabajos han ampliado esta información (Peña & Bárbara, 2004, 2008aCarro & al., 2014;Pardo & al., 2014a, b;, así como detectado nuevas especies formadoras de maërl, como por ejemplo Mesophyllum sphaericum o Phymatolithon lusitanicum . Otros trabajos, en cambio, han estado enfocados hacia la distribución, ecología y conservación de este hábitat en el Atlántico ibérico (Peña & Bárbara, 2006, 2008a, b, 2009, 2010aPeña, 2010).…”
Section: Introductionunclassified